Effects of pre-germinated brown rice on blood glucose and lipid levels in free-living patients with impaired fasting glucose or type 2 diabetes - Hsu, T.F.(Tokushima Univ. (Japan)); Kise, M; Wang, M.F; Ito, Y; Yang, M.D; Aoto, H; Yoshihara, R; Yokoyama, J; Kunii, D; Yamamoto, S (Journal of Nutritional Science and Vitaminology, 2008)
White rice (WR) is made by polishing brown rice (BR) and has lost various nutrients; however, most people prefer it to BR, maybe because of the hardness of BR. Pre-germinated brown rice (PGBR) improves the problem of BR. It is made by soaking BR kernels in water to germinate and becomes softer than BR. In this study we compared the effects of WR and PGBR on blood glucose and lipid concentrations in the impaired fasting glucose (IFG) or type 2 diabetes patients. Six men and 5 women with impaired fasting glucose (IFG) or type 2 diabetes were randomly allocated to 6 wk on WR or PGBR diet separated by a 2 wk washout interval in a crossover design. Each subject was instructed to consume 3 packs of cooked WR or PGBR (180 g/pack) daily in each intervention phase. Blood samples were collected 4 times (in study weeks 0, 6, 8 and 14) for biochemical examination. Blood concentrations of fasting blood glucose, fructosamine, serum total cholesterol and triacylglycerol levels were favorably improved on the PGBR diet (p0.01), but not on the WR diet. The present results suggest that diets including PGBR may be useful to control blood glucose level.